35

√37+√2
убрать иррациональность из знаменателя
((

f3k f3k    3   23.08.2019 21:43    3

Ответы
Sunshinesun88 Sunshinesun88  05.10.2020 15:22

Объяснение:

\frac{35}{\sqrt{37}+\sqrt2}=\frac{35\cdot (\sqrt{37}-\sqrt2)}{(\sqrt{37}+\sqrt2)(\sqrt{37}-\sqrt2)}=\frac{35\cdot (\sqrt{37}-\sqrt2)}{37-2}=\frac{36\cdot (\sqrt{37}-\sqrt2)}{35}=\sqrt{37}-\sqrt2\\\\\\\star \; \; (a-b)(a+b)=a^2-b^2\; \; \star

ПОКАЗАТЬ ОТВЕТЫ
chokopaii chokopaii  05.10.2020 15:22

√37-√2

Объяснение:

35/(√37+√2) = 35(√37-√2)/((√37+√2)(√37-√2)) = 35(√37-√2)/(37-2) = 35(√37-√2)/35 = √37-√2

ПОКАЗАТЬ ОТВЕТЫ